2020
DOI: 10.1186/s41231-020-00073-y
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of melanin and vitamin-D may play a fundamental role in preventing SARS-CoV-2 infections and halt COVID-19 by inactivating furin protease

Abstract: Since the birth of Christ, in these 2019 years, the man on earth has never experienced a survival challenge from any acellular protist compared to SARS-CoV-2. No specific drugs yet been approved. The host immunity is the only alternative to prevent and or reduce the infection and mortality rate as well. Here, a novel mechanism of melanin mediated host immunity is proposed having potent biotechnological prospects in health care management of COVID-19. Vitamin D is known to enhance the rate of melanin synthesis;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 113 publications
0
9
0
2
Order By: Relevance
“…Vitamin D3 has also been observed to promote hBD2 expression in peripheral mononuclear cells in humans, lowering infection rates [ 124 ]. Vitamin D3 has been suggested as a therapeutic method for bacterial infection and viral infections such as COVID-19 [ 125 ]. Additionally, vitamin D3 may be utilized to treat respiratory viral infections as a treatment option because HBD2 is known to be produced in the respiratory tract during viral infections.…”
Section: Regulation Of Amps Expression In the Respiratory Tract And I...mentioning
confidence: 99%
“…Vitamin D3 has also been observed to promote hBD2 expression in peripheral mononuclear cells in humans, lowering infection rates [ 124 ]. Vitamin D3 has been suggested as a therapeutic method for bacterial infection and viral infections such as COVID-19 [ 125 ]. Additionally, vitamin D3 may be utilized to treat respiratory viral infections as a treatment option because HBD2 is known to be produced in the respiratory tract during viral infections.…”
Section: Regulation Of Amps Expression In the Respiratory Tract And I...mentioning
confidence: 99%
“…Кателіцидини характеризуються прямою антимікробною дією на грампозитивні, грамнегативні бактерії, грибки та віруси. Ці пептиди вбивають патогенні мікроорганізми, порушуючи їх клітинні мембрани [66].…”
Section: вітамін D і серцево-судинна системаunclassified
“…VD також перешкоджає утворенню прозапальних цитокінів, таких як TNF-α, IL-8, IL-6, IFN-β та RANTES в епітеліальному шарі легень. Останній цитокін, поряд з IL-6, бере участь у порушенні імунного гомеостазу при інфекції COVID-19 [66].…”
Section: вітамін D і серцево-судинна системаunclassified
“…Estradiol and vitamin D were also able to affect furin’s activity in rat, mouse, and human cells ( Glinsky, 2020 ). The treatment with Vitamin D is still controversial, while some studies have found negative correlation between vitamin D levels and COVID-19 cases ( Ilie et al ., 2020 ) other hypothesis an alleviation on lung inflammation caused by SARS-CoV-2 because vitamin D seems upregulating ACE2 human receptor and decreasing inflammatory cytokines ( Xiao et al ., 2021 ).Since, Vitamin D is known to enhance the rate of melanin synthesis; and this may concurrently regulate the expression of furin expression both vitamin D and melanin may have significant impact in management of COVID-19 ( Paria et al ., 2020 ). Additionally irisin, luteolin, and nafamostat have demonstrated inhibitory activity against furin ( Peng et al ., 2017 ; de Oliveira et al ., 2020 ; Yamamoto M et al ., 2020 ).…”
Section: Pharmacological Interventions In Cellular and Animal Modelsmentioning
confidence: 99%